2014
DOI: 10.1073/pnas.1322910111
|View full text |Cite
|
Sign up to set email alerts
|

The estrogen receptor antagonist ICI 182,780 can act both as an agonist and an inverse agonist when estrogen receptor α AF-2 is modified

Abstract: Significance Estrogen exerts important effects in the skeleton, which are primarily mediated via estrogen receptor (ER)α, which stimulates target gene transcription through two activation functions (AFs), AF-1 in the N-terminal and AF-2 in the ligand-binding domain. Previous studies demonstrate that ERα ligands might act as agonists, partial agonists, or antagonists. We demonstrate that the ERα antagonist ICI 182,780 (ICI) acts in a tissue-dependent manner in mice lacking ERαAF-2, resulting in no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…The fact that GPER activation causes vasodilation is consistent with the hypotensive side effects observed in some patients receiving Faslodex® (Vergote and Abram, 2006) . The understanding of fulvestrant action has however been further complicated by the recent finding that this compound may also act as an ERα agonist when the activation function-2 (AF-2) of ERα is mutated (Borjesson et al, 2011; Moverare-Skrtic et al, 2014). Finally, the question as to whether polymorphisms of the GPER gene, which maps to chromosome 7p22, a locus also associated with resistant arterial hypertension in genetic linkage studies in humans (Lafferty et al, 2000; Haas et al, 2009), may be associated with changes in cardiovascular disease risk, is beginning to be addressed in arterial hypertension (Feldman et al, 2013) as is the relationship of GPER polymorphisms to human seminoma risk (Chevalier et al, 2014).…”
Section: Outlook and Potential Clinical Applicationsmentioning
confidence: 99%
“…The fact that GPER activation causes vasodilation is consistent with the hypotensive side effects observed in some patients receiving Faslodex® (Vergote and Abram, 2006) . The understanding of fulvestrant action has however been further complicated by the recent finding that this compound may also act as an ERα agonist when the activation function-2 (AF-2) of ERα is mutated (Borjesson et al, 2011; Moverare-Skrtic et al, 2014). Finally, the question as to whether polymorphisms of the GPER gene, which maps to chromosome 7p22, a locus also associated with resistant arterial hypertension in genetic linkage studies in humans (Lafferty et al, 2000; Haas et al, 2009), may be associated with changes in cardiovascular disease risk, is beginning to be addressed in arterial hypertension (Feldman et al, 2013) as is the relationship of GPER polymorphisms to human seminoma risk (Chevalier et al, 2014).…”
Section: Outlook and Potential Clinical Applicationsmentioning
confidence: 99%
“…Recent reports reveal increasing complexity of these mechanisms that imply direct and indirect activities on bone cells. 20 The bone anabolic effect of both RLX and estrogen, through direct action on bone cells was previously confirmed in a concentration-dependent manner, and was blocked by the ER antagonist, ICI 164,384. 21 Emerging evidence has shown that inhibition of osteoclastogenesis is the main mechanism by which estrogen and RLX prevent bone loss, directly by potently suppressing osteoclast differentiation induced by the ligand of receptor activator of NF-rB (RANKL) and macrophage-colony stimulating factor (M-CSF), through the classical ER -and in dosedependent manner.…”
Section: Discussionmentioning
confidence: 87%
“…The favorable endometrial safety profile of RLX/CE TSEC, would be attributed to blocking of the estrogeninduced DNA transcription, through competitive binding of RLX to the ER, 20 that has been essentially attributed to the peculiar orientation and interaction of the critical alkylaminoethoxy RLX side-chain with the amino acid aspartate Figure 6 The vaginal parameters in all studied groups. Data are represented as mean ± SD, of 10 rats in each group.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of AF-1 or AF-2 activation or cooperative regulation of ERα AF-1 by AF-2 is still unresolved (Arao et al, 2015). Although the ERα AF-2 mutations (ERaAF-2° and AF2ER) disrupt E2-mediated physiological responses, antagonistic ligands such as fulvestrant and tamoxifen activate AF-1 mediated physiological functions in these mutant mice (Arao et al, 2012; Arao et al, 2011a; Moverare-Skrtic et al, 2014). AF2ER females present with disrupted metabolic phenotypes similar to ERaAF-2° and αERKO mice.…”
Section: Physiological Role Of Erα Transactivation Domains In Metabolismmentioning
confidence: 99%